ANALISIS FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENDAPATAN USAHA TERNAK SAPI LOKAL DI KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI - Haris Susanto; Angga Pramana (Fakultas Pertanian, Universitas Riau, 2021)
Indonesia has a wealth of unique tropical biological resources, an abundance of sunlight, water and soil, as well as a community culture that respects nature, the potential of agriculture sourced from local abundance is enormous. The local cow maintenance system in Kuantan Singingi Regency is still a semi-intensive system. This business is a hereditary business and is a people's farm that generally farmers provide feed in the form of forage in the form of field grass and let the cows graze foraging in grazing areas in the form of plantation land both oil palm and rubber plantations and shrubs that are not cultivated. local cattle farms or kuantan cows are still dominated by small-scale folk farms. In addition, the scale of management is also still a side business that is not balanced with adequate capital and management and working on livestock as a daily activity. The development of local cattle as one of the slaughter cattle is still experiencing many obstacles because of its maintenance which is still traditional, very unprofitable because it does not produce to the maximum. Based on the description above, the study aims to determine the social and economic factors that affect the amount of income earned by local cattle farmers. The results showed that the free variable that has a real effect on the income of local cattle business in Inuman District Kuantan Singingi is the scale of cattle (X1), because it has a P-value smaller than the real level = 0.01 or a confidence level of 99 percent. Sedankan other variables have no real effect on the income of local cattle business in Inuman District Kuantan Singingi. Farmers are expected to increase the scale of the amount of livestock maintenance. So that with the more number of cattle raised, it will be more and more to the income of local cattle business in Inuman District Kuantan Singingi.